2020
DOI: 10.22541/au.159073397.79530772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zone-specific reference ranges of fetal adrenal artery Doppler indices: a longitudinal study

Abstract: Objective: To establish reference ranges of adrenal artery Doppler indices for the the inferior adrenal artery (IAA) and middle adrenal artery (MAA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Rossi et al [41] observed the maximum number of SSA in an individual to be 60, while Toni et al [15] stated that the number of arteries reduced with age due to involution. Recent literature reports that SSA can branch profusely, such that their number could range from 1 to 30 from one or more sources (Table 3) [3,12,42]. In addition, the commonest branching pattern in most studies was reported as 4 to 8 arteries [3,4,12,[43][44][45].…”
Section: Variations Of Superior Suprarenal Artery: With Regards To the Number Of Arteriesmentioning
confidence: 99%
“…Rossi et al [41] observed the maximum number of SSA in an individual to be 60, while Toni et al [15] stated that the number of arteries reduced with age due to involution. Recent literature reports that SSA can branch profusely, such that their number could range from 1 to 30 from one or more sources (Table 3) [3,12,42]. In addition, the commonest branching pattern in most studies was reported as 4 to 8 arteries [3,4,12,[43][44][45].…”
Section: Variations Of Superior Suprarenal Artery: With Regards To the Number Of Arteriesmentioning
confidence: 99%